Mechanical thrombectomy utilising a collateral pathway in a patient with dysgenesis of the internal carotid artery. Issue 1 (February 2019) - Tsukano, Jun; Kurabe, Satoshi; Sugai, Tsutomu; Wada, Manabu; Kumagai, Takashi
We describe a case of acute middle cerebral artery occlusion in a patient with ipsilateral internal carotid artery dysgenesis successfully treated with mechanical thrombectomy utilising a collateral pathway. During the procedure, a triaxial system using a balloon guiding catheter, flexible large lumen aspiration catheter and stent retriever was advanced from the left vertebral artery to the occluded left middle cerebral artery through the left posterior communicating artery. Because proximal aspiration from the balloon guiding catheter alone might have insufficient suction force due to the retrograde blood flow from large vascular communications (e.g. vertebral artery union), the tip of the flexible large lumen aspiration catheter was set at the proximal left middle cerebral artery, and distal aspiration was added during stent retrieval. A thrombolysis in cerebral infarction 2b result was achieved after the first pass. In this case, identification of carotid canal hypoplasia on computed tomography allowed for an immediate attempt of this alternative approach, avoiding a delay in the time to reperfusion.